PENGARUH PEMBERIAN JAMU KUNYIT ASEM TERHADAP PENURUNAN SKALA NYERI DESMINORE PADA REMAJA PUTRI DI PERUMAHAN BUMI SAKINAH LESTARI BOGOR TAHUN 2023 - Sinta Amelia; Rindu Rindu; Mustopa Mustopa (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Introduction: Dysmenorrhea is severe pain or pain felt by a woman in the lower part of her stomach during menstruation and generally occurs on the first day of menstruation/menstruation until the end of menstruation. To overcome this problem, non-pharmacological treatment is needed, namely consuming the herbal medicine turmeric tamarind.Objective: To determine the effect of administering tamarind turmeric herbal medicine on reducing the desminore pain scale in adolescent girls at the Bumi Sakinah Lestari Housing Complex, Bogor.Method: The research design used a pre-experimental method with one group pretest-posttest, with purposive sampling and using Wilcoxon signed rank test data analysis. The research population was female teenagers in Bumi Sakinah Lestari Bogor Housing, the sample size was 20 respondents.Results: The Wilcoxon test obtained a p-value of 0.000 (<0.05), meaning that there was an effect of giving tamarind turmeric herbal medicine on reducing the desminore pain scale in young women in the Bumi Sakinah Lestari Housing Complex, Bogor.Conclusion: There is an effect of giving tamarind turmeric herbal medicine on reducing the desminorrhea pain scale in young women at Bumi Sakinah Lestari Bogor Housing in 2023.